Continuance Intention Customer Analysis On Online Accounting Software Usage - Zulfati imani Syamsu (Syntax Corporation Indonesia, 2020)
Software as a Service (SaaS) is a variant of technology products that are now loved by both personal and business users. SaaS is a software product variant that can be used directly by users, without the need for complicated installation. In the realm of accounting itself, there have been many emerging accounting softwares ranging from those that are offline to online, one of which is Jurnal.id. Jurnal.id is a SaaS platform that presents a variety of digital accounting products that are designed to simplify and accelerate the process of bookkeeping business. This study aims to examine customer continuance intentions on the use of Jurnal.id online accounting software. The variables in this study consisted of perceived usefulness, information quality, service quality system quality, satisfaction, and continuance intention. The population in this study are the users of Jurnal.id Online Accounting Software in the Greater Jakarta area. The sample in this study amounted to 300 people obtained using the Hair Formula. This study uses the Structural Equation Model (SEM) approach using Partial Least Square (PLS) software, the SMART-PLS software version 3.3.2. The results showed that perceived usefulness, system quality, and service quality had a positive effect on satisfaction using Jurnal.id's online accounting software. Simultaneously Satisfaction has a positive effect on continuance intention. However, Information quality does not have a positive effect on satisfaction using online accounting software Jurnal.id